(untitled) (Al-Aasar, 2026)
This article examines the intricate jurisprudential boundaries between Talfeeq (the synthesis of rulings from different schools of thought) and Tattabu’ al-Rukhas (the self-serving pursuit of legal concessions). In the contemporary era, Islamic legal thought is caught between the necessity for Legal Stability, maintained through the tradition of Taqlid (legal conformism), and the demand for Legal Fluidity necessitated by complex modern socio-economic shifts. The primary objective of this research is to establish objective criteria to distinguish between "Permissible Talfeeq" and "Prohibited Concession-Seeking." Utilizing a comparative and analytical methodology, the study evaluates the legal frameworks of three influential contemporary jurists: Dr. Wahbah al-Zuhayli, Dr. Abd al-Karim Zaydan, and Mufti Muhammad Taqi Usmani. Findings reveal a spectrum of methodologies: Al-Zuhayli prioritizes Public Interest (Maslahah) and the removal of hardship, allowing for a broader selection of opinions; Zaydan emphasizes the strength of evidence (Quwwat al-Dalil) as the primary guide for legal movement; whereas Usmani advocates for a restrictive approach, viewing strict adherence to a single school as a necessary mechanism for Sadd al-Dhara’i (blocking the means to evil) against modern intellectual anarchy. The article concludes by proposing a balanced framework grounded in Maqasid al-Shari’ah (the Objectives of Shari’ah), suggesting that Talfeeq be institutionalized through collective expert councils to ensure it remains free from compound invalidation and personal whim.